Achieving food security in Central Asia: current challenges and policy research needs - Babu, Suresh Chandra; Pinstrup-Andersen, Per (Elsevier, 2000)
This paper introduces the papers of this Special Issue on Achieving Food Security in Central Asia. Identifying the current challenges, it enlists the information gaps and policy research needs for accelerating the reform process in the food, agriculture and natural resource sectors of the Central Asian Republics. The paper concludes by calling for identifying policies and institutional arrangements that facilitate economic reforms that will lead to poverty reduction, increased food security, and sustainable use of natural resources.